Treatment Adherence with Early Prescription of Long-Acting Injectable Antipsychotics in Recent-Onset Schizophrenia. (3rd April 2012) - Viala, Annie; Cornic, Françoise; Vacheron, Marie-Noëlle
Abstract : Although response to treatment for the first episode of schizophrenia is generally favourable, nonadherence with the treatment is the first cause of relapse and rehospitalisation within the next few years. Long-acting injectable antipsychotics (LAIAs) combine the advantages of the newer antipsychotics and the long-acting formulation. The evaluation concerns 25 schizophrenic patients hospitalised for the first time, treated with risperidone long-acting injectable (RLAI) associated with reintegration methods, and followed up for at least 18 months. Clinical observation was completed using Clinical Global Impression (CGI) scale and Global Assessment of Functioning (GAF). Clinical improvement was coupled with a good reintegration rate, very few relapse, or rehospitalisation. Bimonthly injection combined with psychosocial methods improved interactive followup, and therefore patients' compliance with the treatment. Treating with LAIA as early as possible, from the first episode if possible, can reduce relapse, number and duration of rehospitalisation, and cognitive symptoms and improve the quality of life and prognosis.